Earthquake Relocation Using Double Difference Method for 2D Modelling of Subducting Slab and Back Arc Thrust in West Nusa Tenggara - Taruna, Rian Mahendra; Banyunegoro, Vrieslend Haris (Jurnal Penelitian Fisika dan Aplikasinya (JPFA), 2018)
West Nusa Tenggara is classified into earthquake prone zone as it is located between subduction and back arc thrust earthquake sources. Accurate hypocenter determination in this area is necessary for strong motion calculation and earthquake source zone modelling. Earthquake relocation in the region is needed to produce a more accurate hypocenter location and 2D modelling of subduction slab and back arc thrust. A double difference method was employed with earthquake data from 2009-2017. The results show better accuracy in the distribution of the travel-time residual. Subduction slab modelling shows a dip value of about 7-13° from a trench to an arc, 49-55° from an arc to a transition zone, and 60-64° dip at a depth of 300 km. Back arc thrust modelling shows a dip value of about 19-28° at a depth of 15-30 km. The results provide a reliable 2D model for subduction slab and back arc thrust in West Nusa Tenggara. Therefore, the developed models can be used as reference for earthquake zones and seismic hazard assessment in West Nusa Tenggara.